2006
DOI: 10.1108/09590550610710246
|View full text |Cite
|
Sign up to set email alerts
|

Sed quis custodiet? Employee theft in UK retailing

Abstract: PurposeEmployee theft is a significant part of retail losses from shrinkage, yet has been comparatively underexplored compared with shoplifting. The purpose of this paper is to assess the impacts of different forms of staff theft and fraud upon retail crime losses and analyse the characteristics of offenders.Design/methodology/approachThe approach is based on a statistical analysis of the details (from retail records) of all staff offenders apprehended for theft by four major UK retailers over a two‐year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…It is not surprising then that trying to understand the particular risk associated with the checkout area is diffi cult to ascertain. Certainly, the problem of ' sweethearting ' at the till, where members of staff will facilitate their friends, family and colleagues to steal products by either not scanning goods through the checkout or providing illegitimate discounts, has long been recognised as a potential source of shrinkage ( Curtis, 1979 ;Carter et al , 1988 ;Bamfi eld, 1998 ;Greenberg, 2002 ;Bamfi eld, 2006 ). Equally, the theft of cash at the till by members of staff is also a perennial problem faced by retailers, although this is perhaps more easily measured and detected than sweethearting, as retailers have been able to adopt more controls relating to the counting and auditing of cash ( Hayes, 2007 ;Sennewald and Christman, 2008 ).…”
Section: Retail Shrinkagementioning
confidence: 99%
“…It is not surprising then that trying to understand the particular risk associated with the checkout area is diffi cult to ascertain. Certainly, the problem of ' sweethearting ' at the till, where members of staff will facilitate their friends, family and colleagues to steal products by either not scanning goods through the checkout or providing illegitimate discounts, has long been recognised as a potential source of shrinkage ( Curtis, 1979 ;Carter et al , 1988 ;Bamfi eld, 1998 ;Greenberg, 2002 ;Bamfi eld, 2006 ). Equally, the theft of cash at the till by members of staff is also a perennial problem faced by retailers, although this is perhaps more easily measured and detected than sweethearting, as retailers have been able to adopt more controls relating to the counting and auditing of cash ( Hayes, 2007 ;Sennewald and Christman, 2008 ).…”
Section: Retail Shrinkagementioning
confidence: 99%
“…The typical perpetrator is described as a drug abuser stealing between £22,000 and £44,000 annually (ibid). Similar to theft of goods during transport, a relatively small number of thefts causes the majority of losses while the majority of thefts corresponds with relatively low loss values (Bamfield 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of employee theft has been conducted in various businesses and industries. In a study within a retail industry, the literature shows that the employee theft situation is intensifying and is a major cause of retail loss (Alstete, 2006;Bamfield, 2006). Despite the perception of shoplifting being high among retailers compared with employee theft, the cost of shoplifting is not as high as the cost of employee theft.…”
Section: Significance Of Employee Theftmentioning
confidence: 99%
“…The concept of concealment by employees, in some cases, makes it more difficult for businesses to detect theft incidents. The extent to which employee theft affects a firm can be difficult to estimate because only a small proportion of employee theft is detected when it occurs (Bamfield, 2006). Unfortunately, the literature indicated that the majority of employee theft is not discovered.…”
Section: Business Response To Employee Theftmentioning
confidence: 99%